Noncommutative configuration space: classical and quantum mechanical aspects - Vanhecke,F. J. (2006)
In this work we examine noncommutativity of position coordinates in classical symplectic mechanics and its quantisation. In coordinates {q i,p k} the canonical symplectic two-form is omega0 = dq i